Psychometric properties of the Connor-Davidson Resilience Scale (CD-RISC) in the Spanish population - García León, Maria Ángeles; González-Gomez, Andrés; Robles-Ortega, Humbelina; Padilla, Jose Luís; Peralta-Ramirez, Isabel (Anales de Psicología / Annals of Psychology, 2018)
Although the number of studies in the literature on the psychometric properties of the CD-RISC measures is remarkably high, there is still a great lack of consensus about its internal structure among the general population. Therefore, the aim of this study has been threefold: to analyze the psychometric properties, explore the factorial structure and calculate percentiles of the Connor-Davidson Resilience Scale (CD-RISC) for a sample of the Spanish population. For this purpose, the study sample consisted of 1119 participants consisting of 324 males and 795 females and they completed the following scales: CD-RISC, Perceived Stress Scale, Multidimensional Scale of Perceived Social Support, General Self-Efficacy Scale, Stress Vulnerability Inventory, Personality Hardiness Questionnaire and the anxiety and depression subscales of the SCL-90-R. In terms of reliability, an adequate Cronbach's coefficient alpha value of .86 was obtained. The evidence for the validity of the internal structure supports the unidimensionality of the CD-RISC measurements, as well as confirming the expected theoretical relationships and correlating with the described measures in the expected direction. Satisfactory results are obtained in the present study that reinforce the usefulness and precision of this scale for its application using the Spanish population, presenting percentiles that can provide guidance in the interpretation and use of the scores with respect to its application in both research and clinical practice.